Effects of Knowledge Sharing Practices in conjunction with Empowerment Program in Adolescent Pregnant Women towards Promoting Exclusive Breastfeeding: a randomized controlled trial - et. al., Jutamart Kupratakul Ph.D, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background and importance of the problem: Even though the best natural diet to feed a baby is "maternal milk," the rate of exclusive breastfeeding in the first six months of postpartum period remains below the threshold of International Health Organization especially in pregnant adolescents. The purpose of the research was to study the effects of the Knowledge Sharing Practices with Empowerment Program in adolescent pregnant women towards promoting exclusive breastfeeding during the first 6months of postpartum period compared to obtaining a standard knowledge program of normal maternal breastfeeding techniques. Instruments and methods: The study was conducted in 10 to 19-year-old pregnant women who were more than 32 weeks pregnant, using randomized controlled trial (RCT), which divided the samples into two groups of the equal number: the study group and the control group. Each group has 40 people. The study group was given a knowledge sharing practices in conjunction with empowerment in pregnant adolescent women towards promoting exclusive breastfeeding as well as techniques to followup during 6 months of postpartum period while the control group received a standard knowledge program of normal maternal breastfeeding techniques and follow-up during the postpartum period. The research tools included a Knowledge Sharing Practices with empowerment, and a strategy to track during the first 6 months of postpartum period, created by the researchers based on the concept and theory of knowledge sharing practice in conjunction with empowerment strategies according to Gibson’s theory (1991) to stimulate exclusive breastfeeding during the first 6 months of postpartum period. The statistics used in the research were paired t-test, unpaired t-test, Chi-square test and multivariate logistic regression analysis. Findings: The exclusive breastfeeding rates during the first six months of postpartum in the study group was statistically significantly higher than the control group at .05 level in the first 14 days (82.5% and 50.0%, P=0.005), the first month (77.5% and 50.0%, P=0.021), the first 2 months (62.5% and 35.0%, P=0.023), first 4 months (35.0% and 7.5%, P=0.008), first 5 months (25.0% and 2.5%, P=0.012) and the first 6 months during postpartum period (40.0% and 5.0%, P=0.002) and the mean score of knowledge , including attitudes and perceptions of self-management competencies in breastfeeding in the study group after being given the program was higher than the control group’s statistically significant at the .05 level (P<0.001). Conclusion of the research: Knowledge Sharing Practices in conjunction with Empowerment Program and follow-up strategies to support postnatal breastfeeding could promote the rate of exclusive breastfeeding of adolescent mothers during the first 6 months of postpartum period, statistically significant at the .05 level